DAMPAK RIBA DALAM KEBIASAAN BERBELANJA PADA KEHIDUPAN MUSLIM DI INDONESIA - Yuni Fatma Sari; Idham Mahrivi; Marliyah Marliyah; Halimatussakdiyah Halimatussakdiyah (Kampus Akademik Publiser, 2024)
The concept of usury adds complexity to transactions, affecting elements likeexchange agreements and individual behaviors in economic activities. Especially inIndonesia, usury significantly influences the spending habits of Muslims, leading to aculture characterized by excessive spending. This behavior not only lowers the value ofproducts but also gives creditors unfair advantages, enabling them to use forcefulmethods in enforcing contracts. This investigation examines the effects of usury on thepurchasing habits of Indonesian Muslims, highlighting its role in promotingextravagance, depreciating goods, and unfairly empowering creditors. By combiningtheoretical analysis with a review of literature, the study elucidates the intricaterelationship between usury and consumer behavior within the Indonesian Muslimcommunity.